2020
DOI: 10.1039/c9se01278h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted HMF production from water-soluble sugars using betaine-based natural deep eutectic solvents (NADES)

Abstract: The combination of a new NADES system and MW irradiation allowed for the preparation of HMF in high yields and in short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…As a result, the HMF yield in the organic phase was better than using just MIBK by 5 %, leading to a 50 % yield (Table 1, entry 8). This is consistent with the HMF extraction test by Gomes et al., which revealed that EtOAc was 6 % better at extracting solvent than MIBK [26] . When using ethyl acetate, 29 % of HMF was not detected either from the organic phase or from DES, which is an approximately similar order of magnitude to the missing 21 % in the MIBK reaction.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…As a result, the HMF yield in the organic phase was better than using just MIBK by 5 %, leading to a 50 % yield (Table 1, entry 8). This is consistent with the HMF extraction test by Gomes et al., which revealed that EtOAc was 6 % better at extracting solvent than MIBK [26] . When using ethyl acetate, 29 % of HMF was not detected either from the organic phase or from DES, which is an approximately similar order of magnitude to the missing 21 % in the MIBK reaction.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, in a study presented by Morais et al., 1 : 3 ChCl/GA DES (with 5 wt.% H 2 O) was more effective than 1 : 2 ChCl/GA DES (with 5 wt.% H 2 O) for producing furfural from xylan [18] . Reaction temperatures were 150, 160, and 170 °C, and reaction times reported in the literature ranged from 2.5 to 25 mins [18,26] . A small quantity of water (0.5 equiv., 2.5 wt.%) was used as part of the DESs because it has been suggested that a small quantity of water weakens the hydrogen bonds between HBD and HBA, making them more available and reactive [27] .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…158 Thus, greener and more energy-efficient methodologies should be developed. [170][171][172][173][174] Besides, levulinic acid (LA) is another important green platform chemical produced using biomass as a feedstock. LA derivatives are more environmentally friendly alternatives to the fossil fuel resources currently used in organic and polymer synthesis and the fuel industry.…”
Section: Production Of Furans (Furfural and 5-hydroxymethyl Furfural) And Carboxylic Acids By Ma-htt Of Biomassmentioning
confidence: 99%